Economic evaluation of a task-shifting intervention for common mental disorders in India - Christine Buttorff; Rebecca S Hock; Helen A Weiss; Smita Naik; Ricardo Araya; Betty R Kirkwood; Daniel Chisholm; Vikram Patel (The World Health Organization, 2012)
OBJECTIVE: To carry out an economic evaluation of a task-shifting intervention for the treatment of depressive and anxiety disorders in primary-care settings in Goa, India. METHODS: Cost-utility and cost-effectiveness analyses based on generalized linear models were performed within a trial set in 24 public and private primary-care facilities. Subjects were randomly assigned to an intervention or a control arm. Eligible subjects in the intervention arm were given psycho-education, case management, interpersonal psychotherapy and/or antidepressants by lay health workers. Subjects in the control arm were treated by physicians. The use of health-care resources, the disability of each subject and degree of psychiatric morbidity, as measured by the Revised Clinical Interview Schedule, were determined at 2, 6 and 12 months. FINDINGS: Complete data, from all three follow-ups, were collected from 1243 (75.4%) and 938 (81.7%) of the subjects enrolled in the study facilities from the public and private sectors, respectively. Within the public facilities, subjects in the intervention arm showed greater improvement in all the health outcomes investigated than those in the control arm. Time costs were also significantly lower in the intervention arm than in the control arm, whereas health system costs in the two arms were similar. Within the private facilities, however, the effectiveness and costs recorded in the two arms were similar. CONCLUSION: Within public primary-care facilities in Goa, the use of lay health workers in the care of subjects with common mental disorders was not only cost-effective but also cost-saving.